Implementation of 21st Century Learning in the Independent Learning Curriculum at SD IT Islamic Center Deli Serdang - Nazmi, Hasa Basri; Ratnasari, Dwi; Zakaria, Abd Razak (Educative: Jurnal Ilmiah Pendidikan, 2023)
The curriculum is present as a guide used by educators where the curriculum has undergone several changes as a form of adaptation to a dynamic era. One of them is by implementing an independent learning curriculum. Thus every school that has implemented an independent learning curriculum that emphasizes learning according to the characteristics of students. Because this curriculum tends to be considered new and is still being implemented in stages. Therefore, this study aims to find out how the implementation of the independent learning curriculum is carried out, find out the obstacles encountered in implementing the independent learning curriculum, and find out how the form of independent curriculum-based learning assessment at SD IT Islamic Center Deli Serdang in 21st century learning. This research is a field research using descriptive qualitative method. Collecting data in this study using interviews, observation and documentation. The results of this study indicate that: 1) there are four policies in the implementation of the independent learning curriculum, namely the National Examination is replaced by a Minimum Competency Assessment and character survey, the National Standardized School Examination is handed over to schools, the simplification of the Lesson Implementation Plan is only one page, and the expansion acceptance of new students. 2) The implementation of the independent learning curriculum in learning is composed of several designs, starting from the introduction, core activities, elaboration, communication and confirmation and finally closing. 3) The learning assessment process at SD IT Islamic Center Deli Serdang carries out several forms of assessment, such as daily assessments in the form of questions or written notes at the end of the semester.